2022
DOI: 10.1039/d1fo02667d
|View full text |Cite
|
Sign up to set email alerts
|

Oligosaccharides derived from Lycium barbarum ameliorate glycolipid metabolism and modulate the gut microbiota community and the faecal metabolites in a type 2 diabetes mouse model: metabolomic bioinformatic analysis

Abstract: Herein, we assessed the effects of Lycium barbarum oligosaccharides (LBO) on the intestinal microenvironment of type 2 diabetes (T2D) mouse model through gut microbiome and metabolomics analysis. We set high...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 79 publications
3
9
0
Order By: Relevance
“…The Goji polysaccharides could remarkably promote the growth of Clostridium cluster , F. prausnitzii and and Roseburia spp., thereby notably increasing the content of butyrate and alleviating IL-10 deficient colitis in mice [ 51 ]. Lycium barbarum oligosaccharides promoted the growth of beneficial bacteria, including Akkermansia , Bacteroides , Lactobacillus and Prevotella , and reduced the symptoms of inflammation, insulin resistance and hyperglycemia in the T2D mouse model [ 52 ]. CMPP were fermented to increase acetic acid, propionic acid and butyric acid during the intake period, stimulating the growth of Akkermansia , Bacteroides , Bifidobacterium , Feacalibacterium , and Roseburia .…”
Section: Resultsmentioning
confidence: 99%
“…The Goji polysaccharides could remarkably promote the growth of Clostridium cluster , F. prausnitzii and and Roseburia spp., thereby notably increasing the content of butyrate and alleviating IL-10 deficient colitis in mice [ 51 ]. Lycium barbarum oligosaccharides promoted the growth of beneficial bacteria, including Akkermansia , Bacteroides , Lactobacillus and Prevotella , and reduced the symptoms of inflammation, insulin resistance and hyperglycemia in the T2D mouse model [ 52 ]. CMPP were fermented to increase acetic acid, propionic acid and butyric acid during the intake period, stimulating the growth of Akkermansia , Bacteroides , Bifidobacterium , Feacalibacterium , and Roseburia .…”
Section: Resultsmentioning
confidence: 99%
“…There is growing evidence indicating that the structural imbalance of the human gut microbiota contributes to the development of T2DM and other metabolic disorders. 16 The gut microbiota is frequently referred to as a "neglected organ". 17 Changes in the gut microbiota have been found to cause T2DM by influencing inflammation, insulin resistance, and aberrant hepatic lipid metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…After the protein was removed with the Sevag reagent (CHCl 3 :n-BuOH = 4:1), the solution was dialyzed and lyophilized to obtain LBP. LBO was extracted from LBP by referring to the method of Liu et al [ 11 ]. Pronase E (Solarbio Technology Co., LTD, Beijing, China), H 2 SO 4 , and trifluoroacetic acid (TFA) were used to degrade L. barbarum polysaccharide, which then underwent desalting and concentration to obtain LBO.…”
Section: Methodsmentioning
confidence: 99%
“…A previous study found that the L. barbarum oligosaccharide (LBO) improves type 2 diabetes. Moreover, LBO can alleviate liver injury by restoring the morphology of hepatocytes and improving hepatic steatosis and inflammation [ 11 ]. The oligosaccharides present in L. barbarum may be potential prebiotics that exhibit hypolipidemic activity, such as lowering total cholesterol levels [ 12 ].…”
Section: Introductionmentioning
confidence: 99%